2008
DOI: 10.1002/rra.1182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of regional factors on zooplankton structure in a saline lowland river: the Salado River (Buenos Aires province, Argentina)

Abstract: Knowledge of regional factors influencing zooplankton structure in a semiarid river must include both the main channel and any tributaries in order to identify spatial and temporal patterns along with the main factor that affect the zooplankton community. Accordingly, seasonal samples were taken during 1997-1999 at 15 stations in the Salado River basin, where 172 species were identified (53 protozoans, 88 rotifers and 31 crustaceans). Conductivity and temperature optima and tolerances were calculated for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
15
1
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 46 publications
8
15
1
15
Order By: Relevance
“…Shiel (2001, 2002) also observate its correlation with high trophic status. K. tropica was mainly abundant at Saladillos River, with a conductivity lower than Salado River, in agreement with Claps et al (2009) who also found it preference for conductivity values lower than 2,000 μS cm −1 . Dodson et al (2007), in a large-scale study showed that the land use has a significant adverse effect on zooplankton species richness in lakes.…”
Section: Discussion and Final Remarkssupporting
confidence: 84%
See 2 more Smart Citations
“…Shiel (2001, 2002) also observate its correlation with high trophic status. K. tropica was mainly abundant at Saladillos River, with a conductivity lower than Salado River, in agreement with Claps et al (2009) who also found it preference for conductivity values lower than 2,000 μS cm −1 . Dodson et al (2007), in a large-scale study showed that the land use has a significant adverse effect on zooplankton species richness in lakes.…”
Section: Discussion and Final Remarkssupporting
confidence: 84%
“…However, the passage of the river through a plain with intense rural activity, determined that the strongly eutrophic character of the studied meandric river enables an increase in zooplankton abundance. This positive relationship between eutrophy and zooplankton abundance has been found in lakes (Whitman et al 2004) and rivers (Claps et al 2009). …”
Section: Discussion and Final Remarksmentioning
confidence: 91%
See 1 more Smart Citation
“…During the LW phase, the zooplankton was represented by few species with extremely high abundances. Planktonic euryhaline species such as the rotifers B. plicatilis, B. ibericus, and B. dimidiatus, and the cyclopoid Metacyclops mendocinus, frequently found in saline lakes (Claps et al 2009;Cirós-Pérez et al 2001;Sterza and Loureiro Fernandes 2006) represented this assemblage. Evidently, the switch from parthenogenetic to sexual reproduction of some of the dominant species found in the lake during LW reflects their adaptation to highly fluctuating environmental conditions, as described by Gyllström and Hansson (2004).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the abundance of microcrustaceans is strongly affected, whereas that of rotifers shows a minor response (Rennella and Quirós 2006;Bonecker et al 2005;Paidere 2009). Since zooplankton species have different tolerance levels to conductivity and pH (Claps et al 2009), hydrology-driven changes of these variables affect species composition. Likewise, the fluctuation in the submerged vegetation, which constitutes a refuge for predators, causes great changes in the zooplankton community composition (Havens et al 2007).…”
Section: Introductionmentioning
confidence: 99%